2020
DOI: 10.1002/pld3.212
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous sodium diethyldithiocarbamate, a Jasmonic acid biosynthesis inhibitor, induced resistance to powdery mildew in wheat

Abstract: Jasmonic acid (JA) is an important plant hormone associated with plant–pathogen defense. To study the role of JA in plant–fungal interactions, we applied a JA biosynthesis inhibitor, sodium diethyldithiocarbamate (DIECA), on wheat leaves. Our results showed that application of 10 mM DIECA 0–2 days before inoculation effectively induced resistance to powdery mildew (Bgt) in wheat. Transcriptome analysis identified 364 up‐regulated and 68 down‐regulated differentially expressed genes (DEGs) in DIECA‐treated leav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…showed that the content of phloridzin significantly increased in apple plants infected with Venturia inaequalis , improving their defense ability. Therefore, we used the melatonin synthesis inhibitor PCPA and JA synthesis inhibitor DIECA to verify the relationship among melatonin, jasmonic acid, and phlorizin in improving the resistance of pear to B. dothidea [ 41 43 ]. After treatment with PCPA and JA, the melatonin content of pear fruit significantly increased, and the fruit regained some resistance to B. dothidea (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…showed that the content of phloridzin significantly increased in apple plants infected with Venturia inaequalis , improving their defense ability. Therefore, we used the melatonin synthesis inhibitor PCPA and JA synthesis inhibitor DIECA to verify the relationship among melatonin, jasmonic acid, and phlorizin in improving the resistance of pear to B. dothidea [ 41 43 ]. After treatment with PCPA and JA, the melatonin content of pear fruit significantly increased, and the fruit regained some resistance to B. dothidea (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The higher abundance of proteins involved in glutathione metabolism, as well as glyoxylate and dicarboxylate metabolism, were also observed in the stipe of H. marmoreus compared with the mycelia and cap (in another reviewed article in JOF). Furthermore, the upregulation of these proteins was also reported in wheat when resistance to powdery mildew was induced by sodium diethyldithiocarbamate [62] and in rhizobacteria promoted rice root [63]. Therefore, further studies are needed to analyze the functions of stress response proteins in the elongation of the fruiting body stipe.…”
Section: Proteomic Analysis Of Protein Expression Profiles In Different Parts Of the S Rugosoannulata Fruiting Bodymentioning
confidence: 94%
“…hordei [158] Foliar spray, Soil drench Jasmonic acid (JA) Nicotiana benthamiana / Manduca sexta [159] Foliar spray Induce oxidative bursts, phytoalexin accumulation, pathogenesis-related proteins accumulation, lignification, cell wall stiffening, decrease malondialdehyde, enhance lipoxygenase and phenylalanine ammonia-lyase, induce resistance-related enzymes, defense-related genes, induce alkaloids and phenolic acids, induce the production of secondary metabolites and volatile compounds, induce the formation of defensive structure, modulate stomatal opening, tendril coiling, root growth inhibition, anther development, fruit ripening, tuber formation, seed germination, senescence, plant responses against wounding. Oryza sativa/Magnaporthe oryzae [160] Root drench Arabidopsis thaliana/Botrytis cinerea [161] Foliar spray Vitis vinifera/Botrytis cinerea [162] Fruit infiltration Solanum tuberosum / Phytophthora infestans [163] Root drench Triticum aestivum/Powdery mildew [164] Foliar spray Actinidia chinensis/Botryosphaeria dothidea [165] Fruit infiltration Amygdalus persica / Rhizopus stolonifera [166] Fruit injection Vigna mungo/Mungbean yellow mosaic India virus [167] Foliar spray Arabidopsis thaliana / Plasmodiophora brassicae [168] Root drench Arabidopsis thaliana, Nicotiana benthamiana, Nicotiana glutinosa, Nicotiana tabacum, Capsicum annum, Solanum lycopersicum/Cucumber mosaic virus, Tobacco mosaic virus, Turnip crinkle virus [169] Seed spray Saccharum officinarum/Pratylenchus zeae, Helicotylenchus spp [170] Root drench Solanum lycopersicum/ Root-knot nematodes [171] Seed spray Phaseolus vulgaris / Sclerotinia sclerotiorum [172] Foliar spray Pennisetum glaucum / ...…”
Section: Plant Hormones and Functional Analogsmentioning
confidence: 99%